If f ( θ ) = 2 cos 2 θ 1 − sin 2 θ + cos 2 θ , then find the value of f ( 1 1 ∘ ) f ( 3 4 ∘ ) .
Also try Tricky Trigonometry-2 and Tricky Trigonometry-3
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given function can be simplified to f ( θ ) = 1 + t a n θ 1 . So f ( θ ) × f ( 4 π − θ ) = 0 . 5 for all values of θ . Hence the required answer is 0 . 5
@Alak Bhattacharya , you should put a backslash "\" in front of all function name such as \tan \theta tan θ . Note that the tan is not italic and that there is a space between tan and theta.
Problem Loading...
Note Loading...
Set Loading...
f ( θ ) = 2 cos 2 θ 1 − sin 2 θ + cos 2 θ = 2 × 1 + t 2 1 − t 2 1 − 1 + t 2 2 t + 1 + t 2 1 − t 2 = 1 + t 1 = 1 + tan θ 1 Let t = tan θ and using half- angle tangent substitution.
Then
f ( 1 1 ∘ ) f ( 3 4 ∘ ) = ( 1 + tan 1 1 ∘ ) ( 1 + tan 3 4 ∘ ) 1 = ( 1 + tan 1 1 ∘ ) ( 1 + tan ( 4 5 ∘ − 1 1 ∘ ) ) 1 = ( 1 + tan 1 1 ∘ ) ( 1 + 1 + tan 1 1 ∘ 1 − tan 1 1 ∘ ) 1 = 2 1 = 0 . 5
Reference: Half-angle tangent substitution